Hormonal and reproductive factors in relation to the risk of rheumatoid arthritis in women: a prospective cohort study with 223 526 participants - Tian Tian; Peng Wang; Jing Ni; Chan-Na Zhao; Hai-Feng Pan; Tian He; Yang Fang; Yi-Sheng He; Ling-Qiong Jiang; Ruo-Di Zhang; Harry Asena Musonye; Hao-Yun Zhao; et al. (RMD Open)
Objective This study aimed to examine rheumatoid arthritis (RA) risk associated with hormonal and reproductive factors in women from the large cohort of the UK Biobank.Methods Data on hormonal and reproductive factors in women were collected from a prospective cohort of 223 526 UK Biobank participants. The potential relationship between reproductive factors and RA risk was assessed using restricted cubic spline. Hazard ratios (HR) were estimated using Cox proportional hazard regressions.Results During a median follow-up of 12.39 years, 3313 women with RA were identified. Age at menarche >14 years was associated with a greater RA risk (HR 1.13, 95% CI 1.02 to 1.26) compared with menarche at 13. The multiple adjusted HR for RA in women with menopause at <45 years was 1.46. Reproductive years <33 increased the risk of RA (HR 1.39, 95% CI 1.21 to 1.59). Compared with those with 2 children, women with ≥4 children were associated with a higher risk of RA (HR 1.18, 95% CI 1.04 to 1.34). Women who had a hysterectomy (HR 1.40, 95% CI 1.25 to 1.56) or oophorectomy (HR 1.21, 95% CI 1.08 to 1.35) had a higher risk of RA than those without a hysterectomy or oophorectomy. Both hormone replacement therapy (HRT) use (HR 1.46, 95% CI 1.35 to 1.57) and HRT duration (HR 1.02, 95% CI 1.01 to 1.03) were associated with a higher risk of RA.Conclusions Some hormonal and reproductive factors were associated with a higher risk of RA. Hormonal and reproductive factors should be considered in risk assessment and formulating management plans in female patients with RA.